BOOK ADVERTISING IN POPULAR LITHUANIAN WOMEN’S MAGAZINES - URBANAVIČIŪTĖ, ASTA (Knygotyra, 2014)
Advertising in press is one of the oldest, most popular and least expensive forms of advertising, and its effectiveness, compared with other forms of advertising, is rather high. In the most general sense, advertising is a profit gained by mass media from advertisements about goods and services. Meanwhile, perception of a book in people’s minds has always been ambivalent: for some people it was and still is associated with exclusively pragmatic goals, in other words, it is a source of business and income. For the other part of society a book is an exceptionally educational part of culture. At any rate, book publishing is a multiple phenomenon, and for everyone involved in this process it gains a different shade of meaning.A more active tradition of advertising in Lithuania has formed since 1992, when an increasing number of various foreign companies started penetrating into the country. This had a direct impact on the increase of advertising in media as well. Since the end of 2008, advertising volume has dropped by about a third, but advertising of books in popular media in principle has not been affected by this.Popular magazines perform an entertaining function and are intended for leisure, thus advertising of books in magazines coincides with their function. Book advertising in magazines has been noticed by 89 percent of potential readers of the popular periodicals. Judging by this, clients of advertising, i.e. publishing companies reach their initial goal: the advertising is seen and analyzed. On the other hand, only 2 percent of respondents have used advertising in press for their own purposes and decided to purchase the book because of advertising.Book advertising in popular periodicals may be perceived in two ways: as an advertising announcement or as a part of editorial article. Most editors seek for the latter comprehension. With regard to a structural plane, book advertising in popular magazines is usually delivered through a short informative message. Instead of illustrations typical to magazines, a photo of the book cover is published. Another expression of advertising is a short interview with a famous person who has read the book. In more rare cases this could be an interview with an author of the book. In this case one can speak about a relation between a book and advertising and discuss whether this case is advertising or just information provision. In very rare cases book extracts are published.With regard to an advertising place of books in the popular magazines, the least attractive space is dedicated to this purpose. Advertising is usually placed at the end of the magazine, at the bottom of the page, on the left page. In other words, exactly in those places where advertising is least effective according to marketing specialists. For most potential readers, book advertising is not the main, but advisory factor while choosing books. Such readers’ conception is rather natural, since book advertising in the popular magazines occupies a relatively peripheral location. Those who wish to receive more information about books should concentrate on literary publications, where more detailed information is provided.